From Moksha to Milton Bradley: The Historical Journey of Snakes and Ladders - Sharma, Meenu (SocioHumania: Journal of Social Humanities Studies, 2025)
This study explores the transformation of Moksha Patam, a traditional Indian board game rooted in spiritual and moral education, into the globally commercialized game Snakes and Ladders. Originally designed to teach concepts like karma and moksha, the game was secularized during British colonialism and later commodified in the West, losing its original cultural and pedagogical meanings. Using a qualitative library research method, the paper analyzes historical texts, colonial records, and contemporary versions to examine how the game’s symbolism has evolved. Despite widespread homogenization, modern adaptations in countries like Indonesia, Pakistan, and Iran reflect local values and current social issues, indicating the game’s ongoing relevance and semiotic flexibility. Recent efforts by Indian educators and NGOs to reintroduce Moksha Patam into schools highlight a broader movement toward cultural reclamation and decolonized education. The study underscores the need to recognize and preserve indigenous knowledge systems in modern learning environments.